A socio-historical analysis of Lukan and Johannine pneumatological conceptions - Chamburuka, Phillemon M. (HTS teologiese studies, 2020)
This article is a socio-historical analysis of Lukan and Johannine pneumatological traditions. It is important to note that these pneumatological traditions are broad in scope and content. This article endeavours to assess the relationship between the Lukan Pentecost (Ac 2:1–13) and the so-called ‘Johannine Pentecost’ (Jn 20:22) and grapples with the reasons why the Fourth Evangelist conception of the bestowing of the Holy Spirit (Paraclete) in John 20:22 is conspicuously different from the Lukan Pentecost in Acts 2:1–13. It is imperative therefore to ascertain whether there was a Galilean Pentecost and a Judean Pentecost. This scholarly debate is far from being settled because of the differences in approaches and theological persuasions, some of which will be discussed. It is concluded that the Lukan and Johannine pneumatological traditions are distinct traditions that were developed to suit the interests and concerns of their respective communities, as well as the thematic interests of the third and fourth evangelists.Contribution: This article provides a scholarly analysis of the relationship of Lukan and Johannine conceptions of the bestowment of the Holy Spirit upon the disciples of Jesus. The article gives hermeneutical insights that are vital in interpreting pneumatological passages from a socio-historical perspective which will aid preachers, seminarians and theologians as they interpret these selected passages.